0128 Mild Upper Airway Obstruction Leads to Increased Energy Intake and Growth Retardation that Persists After the Obstruction Removal. (27th May 2020) - Rotenberg, A; Assadi, M; Agam, N; Segev, Y; Tarasiuk, A
Abstract: Introduction: Whereas pediatric obstructive sleep apnea may cause insufficient body weight gain and growth retardation, in some studies, metabolic syndrome and obesity were observed. Interestingly, treatment by adenotonsillectomy can lead to accelerated weight gain by an unclear mechanism. Here, we explored the effects of moderate upper airway obstruction (AO) and mild AO (mAO) and its removal (OR) on ventilation, resting energy expenditure (REE), food intake and growth during the diurnal cycle, from weaning to adulthood. Methods: The trachea of 22-day-old rats was surgically narrowed to generate AO, mAO, and OR was performed after two weeks on mAO animals. Minute ventilation was recorded by whole body plethysmography and diurnal food intake, and REE was explored with metabolic cages 12 weeks post surgery. Results: Following tracheal narrowing, inspiratory swings in esophageal pressure increased by 177% (p< 0.01) and 36% (p< 0.01) in AO and mAO rats, respectively, and was similar to the controls in the OR group. REE (Kcal/h/kg) was 3.7±0.1, 5.7±0.12 (p< 0.01), 4.1±0.08 (p< 0.01), and 3.6±0.15 in the control, AO, mAO, and OR groups, respectively. Increased EE in the AO and mAO groups was associated with up-regulation of ventilation by 133% and 56%, respectively (p< 0.01). In all groups, energy intake (EE) was higher during a 12 h active period compared to a sleep period (p< 0.01). EE during the lights on of AO and mAO animals increased by 136 % and 126%, respectively, and was similar to the control in the OR group. Active period EE increased by 19% in both obstructed groups (p< 0.01). Active period EE was 16.7 % higher in the OR group despite the normalization of ventilation and tracheal diameter to the control value. Increased REE was associated with hindrance of bone elongation (p< 0.01), and OR partially improved growth. Conclusion: The need to maintain respiratory homeostasis during upper airway obstruction was associated with a persistent increase in energy intake. Surgical intervention may not be sufficient to correct the energy intake elevation, and endocrine regulation of feeding and growth may have greater impacts post intervention. Support: This study was supported by the Israel Science Foundation grant no. 164/2018